Methodology of blended learning of future social workers’ professionally oriented communication in english - Malota, Anastasiia (Social work and education, 2023)
The article substantiates the methodology of blended learning of professionally oriented oral communication for future social workers in English. In the context of the study, blended learning is defined as a technology that provides a balanced combination of traditional classroom learning, online and offline self-study, as well as online synchronous interaction for students to master the necessary knowledge, skills and abilities in the shortest possible time for the purpose of effective intercultural communication in typical professional situations. Blended learning involves: practical training in the classroom, synchronous forms (virtual classes, instant messaging), asynchronous forms (joint creation of documents, e-mail, forums).The expediency of using two models of blended learning – the rotational model in the variant of changing stations and the model of flipped learning – is substantiated. The stages of blended learning are allocated: preparatory, aimed at developing lexical, grammatical, phonetic listening and speaking skills, familiarisation with learning and communication strategies, speech formulas inherent in monologue-message and monologue-explanation, as well as dialogue-agreement and dialogue-discussion; receptive-reproductive, aimed at analysing information, developing skills of introductory, selective and detailed listening, skills of prepared spoken production and spoken interaction, skills of using learning and communication strategies; productive, which involves improving communication skills in communication situations using selected communication strategies and tactics. A system of exercises correlating with the identified stages is proposed. The effectiveness of the author's methodology has been proved experimentally. The obtained results related to first-year students who are not autonomous enough. It is assumed that the results were different for students of senior years, who probably have a higher level of academic autonomy.